Proposal for a framework with distinctive characteristics as a basis for identifying key-points to implementing cost management systems: a theoretical study in half-barren meso-region organization models - Leite, Maria Silene Alexandre; Brito, André de Medeiros; Oliveira, Josenildo Brito de (Revista Gestão da Produção Operações e Sistemas, 2009)
In order to improve half-barren mesoregion economic and social conditions, entities and companies have been making great efforts to offer adequate resources for the sustainable development of local production activities. Companies are trying to raise their competitive capacity and to profit by taking advantage of the region’s poten- tial and resources. In this search, cost management systems become relevant as a result of their importance to company management, because they need to be adjusted to the conditions and characteristics of arrangements established in this region. Therefore, the objective of this article is to discuss organizational arrangement cha- racteristics from a systematic process, generating a theoretical framework with distinct aspects which will be the foundation for implementing cost management systems based on organizational formats established in the half-barren mesoregion. The results are useful to complement and/or adjust cost management systems to orga- nizational arrangements particularities. The methodological procedures were supported by a selection of main concepts: identifying limitations; constructing characteristics; defining distinctive characteristics among arran- gements. The research is classified as basic, qualitative, exploratory and bibliographic. The study was conducted from April to June, 2008. The results helped define the arrangements’ distinctive characteristics. Keywords: Organizational Arrangements, Cost Management Systems, Half-Barren.